ANALISIS PENGARUH LAYANAN, HARGA, DAN KUALITAS PRODUK PAKAIAN WANITA YANG DIJUAL SECARA ONLINE MELALUI GROUP BLACKBERY MESSENGER TERHADAP MINAT BELI KONSUMEN (STUDI KASUS MAHASISWI STIE MANDALA JEMBER) - Putri Dewi Lestari; Muhammad Firdaus; Tamriatin Hidayah (RELASI : JURNAL EKONOMI, 2013)
This study aims: (1) to determine the effect of service, price, and quality of womenswear products  simultaneously to consumers to buy.  (2)  to determine the effect of  the service,  price,  and  quality  of  womenswear  products  partially on consumers to buy. Sampling technique are used snowball sampling. Total sample were  60  respondents who  transact  womenswear  products  through  BlackBerry Messenger  (BBM). The analysis used multiple regression.   The results showed: (1)  service,  price,  and  quality  of  womenswear  sold online  through  Blackberry messenger group simultaneously significantly affect consumer buying interest. (2) Partially, only price variable that significantly influence the consumers to buy.